Standard for Breast Conservation Therapy in the Management of Invasive Breast Carcinoma - Monica Morrow; E. A. Strom; L W Bassett; D. David Dershaw; Barbara Fowble; A E Giuliano; Jay R. Harris; F. O’Malley; Stuart J. Schnitt; S. Eva Singletary; David P. Winchester (2002)
Multidisciplinary guidelines for management of invasive breast carcinoma from the American College of Radiology, the American College of Surgeons, the College of American Pathology, and the Society of Surgical Oncology have been updated to reflect the continuing advances in the diagnosis and treatment of invasive breast cancer. The guidelines provide a framework for clinical decision-making for patients with invasive breast carcinoma based on review of relevant literature and include information on patient selection and evaluation, technical aspects of surgical treatment, techniques of irradiation, and follow-up care.